2008
DOI: 10.1063/1.2836970
|View full text |Cite
|
Sign up to set email alerts
|

The microstructure and electrical transport properties of immiscible copper-niobium alloy thin films

Abstract: Thin film reaction of transition metals with germaniumMutually immiscible in the solid state, copper and niobium exhibit a relatively strong clustering ͑phase separating͒ tendency in the liquid state and can therefore only be alloyed in a highly metastable form: for example, by vapor quenching. We have deposited metastable Cu-Nb alloy thin films with nominal compositions ranging from 5 to 90 at. % Nb by magnetron cosputtering. The microstructure of these films depends strongly on the composition and ranges fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
0
17
1
Order By: Relevance
“…The TEM image and ED pattern show the nanocrystalline character of Nb-rich alloy with an estimated grain size of 7-10 nm. Similar microstructures by TEM of Cu x Nb 1Àx alloys with 5-10 at.% of Nb have been shown by [13,21].…”
Section: Stem and Temmentioning
confidence: 66%
See 3 more Smart Citations
“…The TEM image and ED pattern show the nanocrystalline character of Nb-rich alloy with an estimated grain size of 7-10 nm. Similar microstructures by TEM of Cu x Nb 1Àx alloys with 5-10 at.% of Nb have been shown by [13,21].…”
Section: Stem and Temmentioning
confidence: 66%
“…It is suggested that the solution of Cu in the Nb matrix shifts the Nb (1 1 0) peak to higher angles, which results in a decrease in the lattice parameter. Banerjee et al cited a lattice parameter of 0.325 nm for a Cu-90 at.% Nb [21].…”
Section: Xrd Of the Cu X Nb 1àx Alloysmentioning
confidence: 97%
See 2 more Smart Citations
“…This potential describes short-range interactions using the ZieglerBiersack-Littmark (ZBL) function [22] and is therefore well adapted to simulations of radiation response. Amorphous Cu-Nb has been experimentally synthesized via ion-beam mixing [23,24] and sputter deposition [20,[25][26][27] within the composition range of $35-75% copper [26]. We model a-Cu x Nb 1Àx with x = 0.25, 0.5 and 0.75.…”
Section: Model Systemmentioning
confidence: 99%